Design and feasibility of "PREMATurity as predictor of children's Cardiovascular–renal Health" (PREMATCH): A pilot study. (October 2015) - Raaijmakers, Anke; Petit, Thibault; Gu, Yumei; Zhang, Zhenyu; Wei, Fangfei; Cools, Bjorn; Jacobs, Lotte; Thijs, Lutgarde; Thewissen, Liesbeth; Levtchenko, Elena; Staessen, Jan A.; Allegaert, Karel
Abstract The microvasculature and macrovasculature undergo extensive, organ-specific perinatal maturation. Multiple studies show associations between low birth weight and subsequent cardiovascular dysfunction in adulthood, suggesting that extreme preterm birth interferes with this maturation process. Therefore, we designed PREMATCH (PREMATurity as predictor of Cardiovascular–renal Health) to phenotype the microcirculation and macrocirculation during childhood in former preterm infants. A well-characterized cohort of former extreme preterm birth survivors and gender- and age-matched controls (aged 8–13 years) will be investigated for microvascular and macrovascular structure and function. In addition to cognitive performance and anthropometrics, we will investigate (i) the microvascular structure and function by endothelial function (photoplethysmography), sublingual capillary glycocalyx function (sidestream dark field imaging) and retinal structure (diameters of arterioles and venules); and (ii) the macrovascular phenotype by cardiac and renal ultrasound, repeated blood pressure measurements and arterial pulse-wave recordings. The PREMATCH study is unique in its design, and ongoing recruitment demonstrates excellent feasibility. The expectation is that the results of this study will identify risk factors during childhood for subsequent cardiovascular–renal disease in the adult life of former preterm infants, while further analysis on mediators in neonatal life of this cardiovascular–renal outcome may provide new information on perinatal risk factors.